PENERAPAN PHBS UNTUK MENCEGAH PENULARAN COVID-19 PADA KELAS IBU HAMIL DI POSYANDU YANG ADA DI WILAYAH PUSKESMAS KAWALU KOTA TASIKMALAYA - NENI; LULU YULIANI; ANITA EKA PUTRI; REVI MAINAKI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
PHBS is all health behavior that is carried out with awareness so that family members or families can help themselves in the health sector and play an active role in health activities in the community (DEPKES RI, 2010). PHBS must be implemented in various settings, one of which is PHBS at the Health Care Facility (POSYANDU). Pregnant women are a group of people who are at risk of being vulnerable to various health problems. Among them are susceptible to contracting infectious diseases, one example is currently an outbreak of COVID 19, therefore we are in this dedication will provide education about